Evaluation of Antimicrobial Efficacy of Titanium Dioxide on Dental Plaque Colonisers: An In-vitro Study - Kapil Raju; Shanmuganathan Natrajan; Preetha Krishnamurthy (Journal of Clinical and Diagnostic Research, 2022)
Introduction: Denture Stomatitis (DS), a common inflammatory condition of the denture bearing mucosa amongst denture wearers is strongly related to poor denture hygiene. Various materials have been incorporated into denture base acrylic resins to have an antimicrobial effect. The antimicrobial efficacy of Titanium dioxide (TiO2) on denture base acrylic resins has been demonstrated; however, studies are lacking in assessing the effective dose concentration of TiO2 in inhibiting microorganisms present in denture plaque. Aim: To investigate the effectiveness of TiO2 coating on denture base acrylic resin in inhibiting colonisers of denture plaque. Materials and Methods: The in-vitro study was conducted in the Department of Prosthodontics and Crown & Bridge and Department of Microbiology, Sri Ramachandra Institute of Higher Education and Research, Chennai, Tamil Nadu, India between August 2021 to September 2021. Stock solutions of various concentrations of TiO2 were prepared to evaluate the effective dose concentration. Forty specimens of heat cure acrylic denture base resin were divided into two groups: an uncoated group (n=20) and TiO2 coated group (n=20). They were further subdivided into 4 groups, namely specimens containing Streptococcus sanguinis, Staphylococcus aureus, Candida albicans, and specimens containing a mixture of the above organisms. After inoculating, the specimens were UV treated, incubated for 24 hrs, and then washed with phosphate buffer saline. Subcultures were obtained and microbial growth colonies were measured using automated bacterial colony counter. The obtained results were subjected to statistical analysis (SPSS software version 21) and Mann-Whitney U test to compare between the groups, p value of less than or equal to 0.05 (p≤0.05) was considered significant. Results: Colonisers of denture plaque in the uncoated acrylic group was higher (mean:12973.33, 441998.33, 9126.66, and 13.3 CFU) when compared to the TiO2 coated acrylic resin group (mean:1, 0.99, 1, and 1 CFU). The obtained results between the groups was statistically significant (p≤0.05). Conclusion: TiO2 coating on denture base acrylic resin can inhibit the growth of microorganisms associated with denture plaque.